Perbandingan Simulasi Kontrol Kecepatan Kereta Api Dengan Logika Fuzzy Metode Mamdani dan Sugeno - Apriyanto, R Akbar Nur; Samudra, Daris Itsar (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2022)
A transportation that is currently in great demand by the public is the railway because of its affordable and more convenient price. However, based on data from the Railway Statistics Book, the number of train accidents during 2020 was 18 accidents. The cause of the accident can be caused by several factors including facilities, infrastructure, operator human resources, external and natural factors. Some of the factors that affect, for example , rail conditions and weather. In this study, a comparison of train speed control using the fuzzy mamdani and fuzzy sugeno methods will be discussed to find out the suitable method to control train speed so as to reduce accidents caused by train speeds that are not in accordance with rail and weather conditions. From the results of the study, the results on the sharp bend rails of the mamdani method were 72.7 km / h which exceeded the train speed threshold of 60 km / h while for the sugeno method on sharp bend rails it did not exceed the train speed threshold of 55.7 km / h.